ANALISIS KELAYAKAN LEMBAR KERJA PESERTA DIDIK BERBASIS GUIDED INQUIRY PADA MTS NEGERI 1 LUBUKLINGGAU - Endang Lovisia; Ahmad Amin; Puspita Wahyu Irawan (Irfani, 2025)
The purpose of this study was to determine the feasibility of guided inquiry-based student worksheets on the topics of temperature, heat, and expansion. The approach used in this study was the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Feasibility was tested by asking experts in the fields of subject matter, media, and language to fill out a questionnaire designed to determine the feasibility of the product being developed. The subject matter expert validation scored 43 in the excellent category, the media expert validation scored 48 in the excellent category, and the language expert validation scored 69 in the excellent category, so that this guided inquiry-based student worksheet is considered very feasible and can be used as teaching material by students and teachers. Keywords: Student Worksheet, Guided Inquiry, ADDIE Model